Pijat Bayi Sebagai Terapi Komplementer dalam Meningkatkan Kualitas Tidur Bayi di Kelurahan Salopokko - Ariesty AR; Fitriani Fitriani; Enggar Enggar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Baby massage is one of the treatments which is included in complementary methods, complementary is a non-pharmacological therapy which can be used to improve the quality of baby's sleep. Researchers interviewed 10 mothers of babies, and found 7 mothers whose babies had never been massaged and 3 mothers who had massaged their babies. The aim is to analyze the effect of baby massage as a complementary therapy in improving the quality of baby sleep. Method: This type of research is quantitative research using a quasi-experimental research design with a one group pretest-posttest research design. The research was conducted in Salopokko Village with 10 respondents. The statistical test used in this research is the Wilcoxon test. The results of the research show that there is an influence of Baby Massage on the quality of baby's sleep with the result being a p value = .000 or <0.05, which means that there is an influence of Baby Massage on the quality of baby's sleep. Conclusion Baby massage as a complementary therapy can be an alternative to improve the quality of baby's sleep.